Application of nanotechnologies along the food supply chain - Cruz-Lopes, L. (2022)
Nanoscience and nanotechnology are new fromtiers for this century. Nanotechnology translates into the ability to manipulate the material on a nanoscale. As in other sectors, recent developments in the ﬁ eld of nanoscience and nanotechnology o ﬀ er new opportunities for innovation for food. Nanofoods are considered foods grown, produced, processed or packaged using nanotechnological tools that incorporate nanomaterials to improve nutritional quality, taste or texture, and increase the shelf life of food. Nanotechnology ’ s applications are diverse, going from nanoencapsulated ingredients, such as bioactive compounds, nutrients and food additives that increase thebioavailability of the compounds, to ingredients that constitute nanostructures and nanotextures that provide barriers for physical - chemical protection, which allow modi ﬁ cation of ﬂ avour and odour. Also, has the potential to be used as biosensors to monitor food conditions during storage and transport, through packaging that includes indicators. This review covers the development and use of nanotechnology along the food supply chain, focusing the agricultural production, industrial processing and protection through packaging, as well as addressing the advantages and disadvantages of using this technology.